Regional value chains and development integration in the SADC Region: the case of the pharmaceutical industry - Faydherbe, Sean (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2018)
This thesis investigates how regional value chains (RVCs) can be used to further development integration in the Southern African Development Community (SADC) region with a focus on the pharmaceutical manufacturing industry. The study is motivated by the apparent lack of attention given to the development of the pharmaceutical manufacturing industry in Southern Africa, the region's high disease burden and the identification of the industry as economically and socially important by the SADC (2015) Industrialisation Strategy and Roadmap and the Department of Trade and Industry (DTI) (2017a) Industrial Policy Action Plan (IPAP). At the same time, South Africa and other countries in the region are exploring alternative approaches to regional integration, given the failure or stagnation of numerous formal integration arrangements throughout Africa, which have often lead to polarised rather than balanced development. This thesis argues that the development of RVCs within SADC may be an effective tool for development integration in the region, particularly in sectors such as pharmaceuticals. The study employs a value chain framework for the analysis and discusses development integration options, drawing on the East Asian experience with RVCs and on case studies involving India in the case of the pharmaceutical industry. It provides a sector profile of the industry in South Africa, due to its dominant status in the region, and also of Zimbabwe, due to that country's potential to become a pharmaceutical industry leader in the region once again. The thesis first explores the important theoretical aspects underlying value chain analysis, namely governance and upgrading, while also outlining the rise of global value chains (GVCs). It analyses the complex relationships between RVCs and GVCs, and RVCs and regional integration. From this it concludes that RVCs are a stepping stone to participation in GVCs and that RVCs should be promoted within a development integration framework through strong regional cooperation. Value chain analysis is applied to the entire pharmaceutical manufacturing industry with a focus on SADC. The thesis examines how the sector is evolving with manufacturing multinational corporations (MNCs) outsourcing production and setting up centres of excellence in regional production hubs. The study argues that with the application of recommended policies, RVCs in sectors such as pharmaceutical manufacturing may provide a tool for achieving balanced development in the region. However, the study also finds that the pharmaceutical industry in SADC lags a long way behind the rest of the world and that many countries and firms will need to begin at the bottom of the value chain, with formulation, in order to contribute to the development of RVCs. The thesis concludes with recommendations on what policies are needed to foster the growth and development of pharmaceutical RVCs in the SADC region. These include strengthening public procurement, providing incentives for investment into the industry, incremental production and incremental export volumes, as well as certainty and predictability around the regulatory and business environment. Further, policy should aim to construct synergies and linkages on the ground between health systems and industrial developments; regulate service links important to pharmaceutical manufacturing; develop a coherent regional policy agenda; remove unnecessary non-tariff barriers to trade in the region and, in line with development integration, implement trade policy along with trade infrastructure that is efficient and includes airports, rail, roads and ports, as well as effective access to the internet.
Keywords: Pharmaceutical industry -- Africa, Southern; Southern African Development Community; Africa, Southern -- Economic integration; Regional value chains (RVCs); Global value chains (GVCs)